Preparation, Characterisation and Bioactivity Evaluation of Curcumin-Loaded Poly (Lactic-co-Glycolic Acid) Nanoparticles - Muhammad Haziq Ezzani; Deny Susanti; Muhammad Taher; Syamsudin Abdilah (IIUM Press, International Islamic University Malaysia, 2024)
Background: One of the main challenges with curcumin is its hydrophobic nature, which limits its solubility and bioavailability. This issue can be addressed by using poly (lactic-co-glycolic acid) (PLGA) nanoparticles (NPs). The small size and large surface area of these NPs significantly enhance drug delivery systems by improving the solubility and bioavailability of the drug. Objective: This project focuses on the preparation, characterization, and bioactivity evaluation of curcumin loaded in PLGA NPs, intended for the delivery of curcumin extracted from Curcuma xanthorrhiza, commonly known as 'temulawak' or 'Java turmeric'. Methodology: Curcumin was extracted and stored at 4?C for testing. PLGA-curcumin NPs were synthesized using the single emulsion method. Nanoparticle morphology was analyzed using SEM, while particle size and zeta potential were measured with a Zetasizer. Entrapment efficiency and drug loading capacity were calculated. In vitro release studies in phosphate buffer were conducted using UV-visible spectrophotometry. The cytotoxicity of the curcumin-loaded NPs was tested on MCF-7 breast cancer cells using the MTT assay. Statistical analyses were performed using Minitab 14, and Microsoft Excel was used for graphical representations, with significance set at p < 0.05. Results: The mean particle size of the curcumin NPs was 498.9 nm ± 597.4 nm. The entrapment efficiency and drug loading capacity were 50% and 5%, respectively. The average zeta potential was recorded as -28.7 mV ± 6.19 mV.  The in vitro release study did not produce significant results as low concentrations of curcumin were detected. However, the bioactivity of the curcumin-loaded PLGA NPs demonstrated lower cell viability compared to the curcumin extract, suggesting that the PLGA formulation is more effective at inducing cancer cell death. This indicates its potential as a more efficient therapeutic option in cancer treatment. Conclusion: The single emulsion method managed to produce nano-sized particles with good zeta potential and bioactivity on MCF-7 cells. However, further study needs to be done to produce better formulation which can increase entrapment efficiency, drug loading capacity and also in vitro release profile.